Demonstrating impact: Lessons learned from the Queensland Aboriginal and Islander Health Council's AOD-Our-Way program - Cartwright, Kimberly; Gray, Dennis; Fewings, E. (Molecular Diversity Preservation International (MDPI), 2018)
In this paper, we describe the innovative way in which the Queensland Aboriginal and Islander Health Council uses â€œclicker technologyâ€? to gather data to report on the key performance indicators of its â€œAOD-our-wayâ€? program, and how, with the subsequent combination of those data with other performance measures, it was possible to go beyond the initial evaluation. The paper also illustrates how the application of survey research methods could further enable enhanced reporting of program outcomes and impacts in an Indigenous context where Indigenous community controlled organisations want to build the evidence base for the issues they care about and ultimately drive their own research agendas.